Concept of Remuneration and Management Behavior Evaluation in Indonesia - Sarah Yuliarini; Ku Nor Izah Bt Ku Ismail; Tantri Bararoh (Asian Journal of Accounting Research, 2017)
Environmental Accounting (EA) practices have developed rapidly in some countries and have a positive impact on their organizations. Sustainability report (SR) as an indicator of EA practices helps company gain a better reputation and it is set by management. However, some ASEAN countries including Indonesia do not have relevant accounting standards on the environment. EA practice is still not widely known in Indonesia, although, internationally there have been standards that provide guidelines for aspect of the environment such as the Global Reporting Initiative (GRI). Another aspect in GRI is remuneration. Remuneration is part of personnel cost which is a motivation about the positive effects of EA practices to disclose management concern. This research introduces a tool to evaluate a remuneration structure and the consistency of EA practices in the Sustainability Report.